Physical and cognitive cycling performance wearing a training mask - Salas-Montoro, J.-A.; Ramírez-Lechuga, J.; Zabala, M. (European Journal of Human Movement, 2023)
Training mask is a respiratory muscle training device, although it was initially advertised as altitude simulators. The aim of the study was to assess the acute effects of wearing a training masks on physical and cognitive performance in cyclists. Twenty physically active subjects performed two graded exercise tests (GXT) until exhaustion, wearing and not wearing a mask, in counterbalanced order. Immediately after the GXT, they performed a cognitive task on a computer. Power, heart rate, lactate, Rating of Perceived Effort (RPE), peripheral oxygen saturation, lung capacity and cognitive variables (reaction time and response accuracy) were measured. Final power was 14.5 % lower when wearing a mask (p < 0.001; ES = 1.515). Heart rate (p = 0.002; ES = 0.790), lactate (p = 0.002; ES = 0.870), and RPE (p = 0.008; ES = 0.879) were also lower at the end of the mask test. However, in the intermediate stages of the test, at the same intensity, there was no difference in heart rate, while RPE was higher with mask. There were no differences between conditions in peripheral oxygen saturation or cognitive variables. In conclusion, the use of a training mask limits maximal aerobic performance, but there are no differences in cognitive variables or physiological parameters at the same intensity.